Sociodemographic and Lifestyle Factors in Relation to Gastric Cancer in a High-Risk Region of China: A Matched Case–Control Study. (2nd April 2020) - Lin, Yulan; Wu, Chuancheng; Yan, Wei; Guo, Saixiong; Lin, Su; Liu, Baoying
Abstract: Objectives: To explore the role of sociodemographic and lifestyle factors in the development of gastric cancer in a high-risk region of China. Methods: In a case–control study, all newly diagnosed patients with gastric cancer were compared with healthy controls matched (1:1) by sex, age (±3 years), and place of residence during 2013–2017. Results: A total of 622 gastric cancer and 622 healthy controls were included. Larger household size (>4 family members) appeared to decrease gastric cancer risk for Helicobacter pylori -negative ones (odd ratio = 0.43, 95% CI = 0.26–0.70). Similarly, longer refrigerator ownership was associated with a 67% decreased risk in H. pylori -negative group (95% CI = 0.15–0.77). Participants with a family history of gastric cancer had nearly fivefold higher risk (odd ratio = 4.88, 95% CI = 2.49–9.55). Smoking attributed to 83% increased risk (odd ratio = 1.83, 95% CI = 1.19–2.80). Tea consumption dramatically decreased risk in whole study population (odd ratio = 0.28, 95% CI = 0.17–0.45). Conclusions: In summary, family history, smoking, H. pylori -related chronic atrophic gastritis, and H. pylori infection were positively associated with gastric cancer. Whereas, tea consumption and refrigerator use negatively associated with gastric cancer and could be promoted to reduce gastric cancer rate in high-risk populations, especially in the developing regions.